Kawasaki disease shock syndrome: a severe form of Kawasaki disease - İşgüder, Rana; Doksöz, Önder; Bağ, Özlem; Ağın, Hasan; Meşe, Timur; Karaarslan, Ünal Utku; Devrim, İlker (The Turkish Journal of Pediatrics, 2013)
Kawasaki disease is a systemic vasculitis, primarily encountered in children. Its clinical presentation is well known, and coronary artery abnormalities are classical complications. Shock is not a common form of presentation of the disease. We report a case who presented with shock due to Kawasaki disease in accordance with the recently defined 'Kawasaki disease shock syndrome'. In pediatric intensive care units, Kawasaki disease shock syndrome may be misdiagnosed as toxic shock syndrome. Intensivists and emergency room physicians should be aware of this uncommon presentation and perform an echocardiography to search for coronary involvement in case of clinical doubt.